Case report: Online eye movement desensitization and reprocessing approach in children: a case series - Citil Akyol, Canan; Kutlu, Mustafa; Korkmazlar, Ümran (Frontiers in Psychiatry, 2024)
Objective The aim of this study was to examine the use of Eye Movement Desensitization and Reprocessing (EMDR) in online counseling for children with single-incident trauma. Method A qualitative case study method was employed. The research was conducted with two volunteering children and their parents. The sessions were transcribed by the authors, and code names (Ipek and Eylül) were assigned to protect the participants’ identities. İpek’s traumatic memory was explored through drawing pictures with tactile bilateral stimuli and Eylül’s traumatic experience was addressed using tactile bilateral stimuli during the EMDR therapeutic story technique. The Child Revised Impact of Events Scale (CRIES-8) was used for pre-test, post-test, and follow-up testing to support the session descriptions. Results The results indicated that post-traumatic symptoms were reduced and remained at a low level for an extended period in both clients. Conclusions It is suggested that future studies should explore various bilateral stimulation methods in online EMDR, conduct larger-scale studies with children who have experienced different types of traumatic events, and investigate the impact of various EMDR protocols on children.